Randomized, double-blind, placebo-controlled, multicenter study of siltuximab in high-risk smoldering multiple myeloma - Brighton, Timothy; Khot, Amit; Harrison, Simon J.; Ghez, David; Weiss, Brendan M.; Kirsch, Andreas; Magen, Hila; Gironella, Mercedes; Oriol, Albert; Streetly, Matthew; Kranenburg, Britte; Qin, Xiang; et al. (Clinical cancer research, 2019)
Purpose: Interleukin-6 is important for the growth and survival of myeloma cells. This study evaluated blocking IL-6 with siltuximab to delay the transition from high-risk smoldering (SMM) to multiple myeloma (MM). Experimental Design: In a randomized, double-blind, placebo-controlled, multicenter study, 85 patients with high-risk SMM were randomized to 15 mg/kg siltuximab (43 patients) or placebo (42 patients). The primary endpoint was 1-year PFS rate, based on IMWG CRAB criteria. Secondary endpoints included progressive disease indicator rate, PFS and safety. Results: Median age was 62 years (range: 21-84); 57% were male and 87% had a baseline ECOG score of 0. The 1-year PFS rate was 84.5% (siltuximab) and 74.4% (placebo). After a median follow-up of 29.2 months, 32.6% of PFS events occurred with siltuximab and 42.9% with placebo. Median PFS was not reached with siltuximab but was 23.5 months with placebo [HR 0.50 (95% CI: 0.24,1.04), p=0.0597]. The safety profile of siltuximab was comparable to placebo. Most AEs in the siltuximab group were Grade 2/3, most common SAEs were infections/infestations, and renal/urinary disorders. Mortality (3-siltuximab, 4-placebo) was low in both groups. Conclusions: Although this study did not meet the prespecified protocol hypothesis criteria, data suggest that siltuximab may delay the progression of high-risk SMM.